Use of Adcon L and clinical outcome in surgical lumbar pathology - Casallo Quiliano , Carlos (2013)
Postoperative peridural fibrosis is considered a major causative factor of Failed Back syndrome, and a bioresorbable gel was found to prevent the formation of postoperative scar. The aim of this work is to evaluate the clinic and radiologic outcome of patients underwent lumbar surgery who received Adcon L gel. Patients treated surgically for lumbar discopathy, stenosis, or fibrosis between January, 2007 and July, 2009, were included in this study, receiving Adcon L gel. Of 71 patients, only 65 had a 6 month follow-up. 98.4 % of patients submitted to first surgery and 66.6 % of the submitted ones to second surgery had good outcome. All 65 studied patients had none or minimal peridural scar in MRI controls. The ADCON L gel is an effective instrument to prevent peridural scar and to have a good clinical outcome in patients in whom lumbar surgery was performed.